Les données entre normalisation et territoire : la construction de la trame verte et bleue - Pierre Alphandéry; Agnès Fortier; Anne Sourdril (Développement Durable et Territoires)
The greenways identification process leaves an important place to the use of knowledge. Ecological but also territorial dimensions should be linked up along with different types of knowledge – scientific, managerial or local. Through the case study of a modeling work ordered by a Parc Naturel Regional to a research consultancy we analyzed how the chosen methods keep local sources of information away. Overall we consider the place given to the quantitative data in a world obsessed by performance and transparency. This paper outlines ways to favor discussions and to take into consideration knowledge diversity.